Validation and error assessment of the mobile tracer gas dispersion method for measurement of fugitive emissions from area sources. (January 2019) - Fredenslund, A.M.; Rees-White, T.C.; Beaven, R.P.; Delre, A.; Finlayson, A.; Helmore, J.; Allen, G.; Scheutz, C.
Highlights: Controlled release tests were carried out to validate the tracer gas dispersion method. Two teams performed measurements separately using two instruments. Five calculation methods were used to determine target gas to tracer gas ratios. An integrated cross plume concentration calculation method yielded lowest errors. Measurement errors were between −18% and 15% when using the best method. Abstract: A controlled release test was carried out to assess the accuracy of the tracer gas dispersion method, which is used to measure whole-site landfill methane (CH4 ) emissions as well as fugitive emissions from other area sources. Two teams performed measurements using analytical instruments installed in two vehicles, to measure downwind concentrations of target (CH4 ) and tracer gases at distances of 1.2–3.5 km from the release locations. The controlled target gas release rates were either 5.3 or 10.9 kg CH4 h −1, and target and tracer gases were released at distances between 12 m and 140 m from each other. Five measurement campaigns were performed, where the plume was traversed between 2 and 31 times. The measured target gas emissions agreed well with the controlled releases, with rate differences no greater than 1.1 kg CH4 h −1 for Team A and 1.0 kg CH4 h −1 for Team B when quantifying a controlled release of 10.9 kg CH4 h −1 . This corresponds to a maximum error of ±10%. A larger error of up to 18% was seen in the campaign with a lower target gas release rate (5.3 kg CH4 h −1 ). Using a cross plume integration method to calculate tracer gas to target gas ratios provided the most accurate results (lowest error), whereas larger errors (up to 49%) were observed when using other calculation methods. By establishment of an error budget and comparison with the measured error based on the release test, it could be concluded that following best practice when performing measurements, the overall error of a tracer gas dispersion measurement is very likely to be less than 20%.